العلاقة بين مشاركة الكادر التمريضي في قرارات الرعاية السريرية ورضاهم عن تلك المشاركة (Latakia University Journal -Medical Sciences Series, 2019)
The study aimed to determine the relationship between participation of nursing staff in the decisions of clinical care of patients and their satisfaction with those participating in the departments of ambulance and intensive care at Tishreen University Hospital and Al- Wattany Hospital in Lattakia. The sample consisted of (72) nurses from both hospitals (42 nurses from Tishreen University Hospital and 30 nurses from Al- Wattany Hospital) who were presented during the data collection period (convenience sample). The researcher used a questionnaire of nursing staff's participation in clinical care decisions by Adam & Osborne (1997) and nursing staff's satisfaction with participation in clinical care decisions by Bucknall & Thomas (1996) to collect research data. After the data were unloaded, they were statistically processed and tabulated using SPSS version 20. The most important results of the study were that the level of nursing staff' s participation in clinical care decisions in the departments of ambulances and intensive care at Tishreen University Hospital and Al- Wattany Hospital was weak, while the level of nursing staff 's satisfaction with participating in clinical care decisions was moderate. There was no statistically significant relationship between nursing staff's participation in the clinical care decisions of the patients and their satisfaction with such participation. هدفت الدراسة إلى تحديد العلاقة بين مشاركة الكادر التمريضي في قرارات الرعاية السريرية للمرضى ورضاهم عن تلك المشاركة في أقسام الإسعاف والعناية المشددة في مشفى تشرين الجامعي والمشفى الوطني في اللاذقية. حيث تكونت العينة من (72) ممرض وممرضة من كلا المشفيين (42 ممرض/ة من مشفى تشرين الجامعي و 30 ممرض/ة من المشفى الوطني) ممن تواجدوا أثناء فترة تجميع البيانات (العينة المتاحة). استخدمت الباحثة استبيان مشاركة الكادر التمريضي في قرارات الرعاية السريرية لـ Adam & Osborne (1997) , واستبيان رضا الكادر التمريضي عن مشاركته في قرارات الرعاية السريرية لـ Bucknall & Thomas (1996) لجمع البيانات المتعلقة بالبحث، وبعد تفريغ البيانات تمت معالجتها إحصائياً وجدولتها باستخدام البرنامج الاحصائي SPSS النسخة 20. كان من أهم النتائج: أن مستوى مشاركة الكادر التمريضي في قرارات الرعاية السريرية في أقسام الإسعاف والعناية المشددة في مشفى تشرين الجامعي والمشفى الوطني كان ضعيفاً، بينما مستوى رضا الكادر التمريضي عن مشاركته في قرارات الرعاية السريرية كان متوسطاً، ولم توجد علاقة ذات دلالة احصائية بين مشاركة الكادر التمريضي في قرارات الرعاية السريرية للمرضى وبين رضاهم عن تلك المشاركة.